2022
DOI: 10.25222/larr.89
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Polarized Landscapes and a New Approach to Urban Inequality

Abstract: Displays of wealth and opulence in the face of dire need and poverty have become commonplace as the rich and the poor increasingly share city spaces around the globe. Research shows that it is the perception of inequality, more than raw measures of inequality, that has important political consequences and that is most concerning for social well-being. In this article, I propose a theoretical move from a general, statistically driven conceptualization of inequality to a spatially informed concept that recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 48 publications
0
4
0
2
Order By: Relevance
“…La producción de uno requiere necesariamente la creación del otro, tanto en términos concretos (los trabajadores deben producir algo para los consumidores) como simbólicos (nadie es pobre hasta que se compara con alguien más rico). En otras palabras, de no existir la riqueza, la pobreza no sería una condición de exclusión, sino una forma de vida (Dinzey-Flores, 2017). Por lo tanto, la pobreza no es una condición autónoma; más bien, constituye la manifestación de un conjunto de relaciones entre pobres y ricos (Bourdieu y Wacquant, 1992;Elias, 1991;Emirbayer, 1997;Marx, 1993Marx, [1858).…”
Section: Estudiando a Los De Arribaunclassified
“…La producción de uno requiere necesariamente la creación del otro, tanto en términos concretos (los trabajadores deben producir algo para los consumidores) como simbólicos (nadie es pobre hasta que se compara con alguien más rico). En otras palabras, de no existir la riqueza, la pobreza no sería una condición de exclusión, sino una forma de vida (Dinzey-Flores, 2017). Por lo tanto, la pobreza no es una condición autónoma; más bien, constituye la manifestación de un conjunto de relaciones entre pobres y ricos (Bourdieu y Wacquant, 1992;Elias, 1991;Emirbayer, 1997;Marx, 1993Marx, [1858).…”
Section: Estudiando a Los De Arribaunclassified
“…The role of neoliberal policy in the creation and transformation of urban space is well documented (Peck 2004;Dinzey-Flores 2017;Goldstein 2004) and best conceptualized as policy aimed at three specific goals (Leitner et al 2007); (1) shifting the city's focus to the creation and expansion of the private sector, or what Emerson and Smiley (2018) call a "market city," (2) the privatization or semi-privatization of municipal services, and (3) the fostering of urban citizenship that emphasizes the need for individuals to behave responsibly and contribute positively to the economic welfare of the city. The touristification of urban centers can be understood as a kind of neoliberal economic development strategy in which a city engages in both public and private investment in tourism via the growth of the hospitality industry, the revitalization of public spaces for private use, and the marketing of a city's history and cultural heritage for consumption (Little 2015;Guardado 2015;Gregory 2007).…”
Section: Cultures Of Contestation Under Neoliberalismmentioning
confidence: 99%
“…He concluded that people use malls to satisfy different types of needs: from purchasing to self-expressing and keeping familiar, romantic and social relationships. Dinzey-Flores analyzed the antagonism between malls and poverty in Puerto Rico [23], which has also been seen (more violently) in Brazil [24].…”
Section: Related Workmentioning
confidence: 99%